Stress and its Study in Banking Sector of India and Abroad - Ramananda Singh, H.; Dutta, Sonit (Prabandhan: Indian Journal of Management, 2011)
Of late, stress has become a corporate buzzword. Organizations and employees are experiencing the effects of stress. There is a common belief that stress is a negative consequence of modern living. But this assumption is not always true. The effects of stress may be positive or negative. Research evidence shows that stress is both helpful and harmful to task performance. Thus, stress is both a friend and a foe .Eustress or the positive stress means good things. Eustress denotes the presence of optimum level of stress in an individual which contributes positively to his performance. It is healthy, positive and constructive outcome of stressful events and the stress response. An optimum level of stress is required for organizational productivity. Distress or the negative stress means bad things or bad stress. This distress has negative influence and shows effects on individual, family and organization. It has harmful psychological and physiological effects on employees. It reduces performance of the employees and thus leads to low productivity. Employee turnover, absenteeism and high labour cost are other symptoms of distress. According to Barden (2001), negative stress is becoming a major illness in the work environment, and it can debilitate employees and be costly to employers. Thus, it is the responsibility of the managers to identify those suffering from negative consequences of stress and implement appropriate strategy as a defense against stress.This paper attempts to highlight the historical background of stress and its study in the Banking Sectors of India and abroad.